2017
DOI: 10.1158/1078-0432.ccr-16-3063
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge for Development of Valuable Immuno-oncology Biomarkers

Abstract: The development of immunotherapy is an important breakthrough for the treatment of cancer, with anti-tumor efficacy observed in a wide variety of tumors. To optimize immunotherapy use, approaches must be developed to identify which patients are likely to achieve benefit. To minimize therapeutic toxicities and costs, understanding the ideal choice and sequencing of the numerous immuno-oncology agents available for individual patients is thus critical, but fraught with challenges. The immune tumor microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 73 publications
0
68
1
Order By: Relevance
“…Further study of effective PD biomarkers for response in early-phase I-O trials will be the key for future determination of I-O early efficacy endpoints and faster clinical development of this class of drug. Comprehensive discussion of biomarker approaches is beyond the scope of this paper; however, we recommend the companion article in this series for an in-depth review of the topic (56). …”
Section: Traditional Endpointsmentioning
confidence: 99%
“…Further study of effective PD biomarkers for response in early-phase I-O trials will be the key for future determination of I-O early efficacy endpoints and faster clinical development of this class of drug. Comprehensive discussion of biomarker approaches is beyond the scope of this paper; however, we recommend the companion article in this series for an in-depth review of the topic (56). …”
Section: Traditional Endpointsmentioning
confidence: 99%
“…Predictive biomarkers of response to ICIs need to be further studied and incorporated into trials and are discussed in the series (see accompanying article by Mehnert and colleagues, ref. 58). Also, some have observed that a subset of patients develop "hyperprogression" defined by rapid progression of disease after initiation of ICI therapy (59).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, immunotherapies have the potential to induce not only sustained, long-term benefits, but also lingering adverse effects. With these features in consideration, three articles in this CCR Focus examine conventional elements of clinical trials – endpoints, biomarkers and combination strategies – in the context of immunotherapy to highlight where standard principles prevail and where innovations are needed (1–3). The limitations and challenges encountered thus far in the design, implementation, and integration of immunotherapy clinical trials are discussed in the final article of this series (4).…”
Section: Introductionmentioning
confidence: 99%
“…examine the challenges of utilizing the traditional endpoints of ORR, PFS and OS in immuno-oncology clinical trials. Further, as discussed by Mehnert et al (3), selection biomarkers are not yet universally validated to accurately predict response or resistance to immune checkpoint inhibitors. PD-L1 expression on tumor or immune cells by immunohistochemistry has been the most frequently considered, although this biomarker is confounded by the multiple antibodies and disparate scoring criteria that accompany the various PD-1/PD-L1 inhibitors (13).…”
Section: Introductionmentioning
confidence: 99%